Sensor Sensibility—HIV-1 and the Innate Immune Response - Yin, Xin (Cells, 2020)
Innate immunity represents the human immune system’s first line of defense against a pathogenic intruder and is initiated by the recognition of conserved molecular structures known as pathogen-associated molecular patterns (PAMPs) by specialized cellular sensors, called pattern recognition receptors (PRRs). Human immunodeficiency virus type 1 (HIV-1) is a unique human RNA virus that causes acquired immunodeficiency syndrome (AIDS) in infected individuals. During the replication cycle, HIV-1 undergoes reverse transcription of its RNA genome and integrates the resulting DNA into the human genome. Subsequently, transcription of the integrated provirus results in production of new virions and spreading infection of the virus. Throughout the viral replication cycle, numerous nucleic acid derived PAMPs can be recognized by a diverse set of innate immune sensors in infected cells. However, HIV-1 has evolved efficient strategies to evade or counteract this immune surveillance and the downstream responses. Understanding the molecular underpinnings of the concerted actions of the innate immune system, as well as the corresponding viral evasion mechanisms during infection, is critical to understanding HIV-1 transmission and pathogenesis, and may provide important guidance for the design of appropriate adjuvant and vaccine strategies. Here, we summarize current knowledge of the molecular basis for sensing HIV-1 in human cells, including CD4(+) T cells, dendritic cells, and macrophages. Furthermore, we discuss the underlying mechanisms by which innate sensing is regulated, and describe the strategies developed by HIV-1 to evade sensing and immune responses.